2017
DOI: 10.1177/0969776417719489
|View full text |Cite
|
Sign up to set email alerts
|

Neighbourhood events and the visibilisation of everyday life: The cases of Turro (Milan) and Norra Fäladen (Lund)

Abstract: While scholars agree on the reasons behind the current proliferation of urban, small-scale, pre-organised events, the implication of these events for public life is more controversial, and involves polarised debates between enthusiasts and critics. This paper develops an international comparison between one city district in Milan (Italy) and one in Lund (Sweden), in order to explore how the variety of events that took place there between 2013 and 2015 possibly affected the local and on-going everyday public li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Struggles over events generate debate in the public sphere about what and who parks are for -'visibilising the nature of the territorial complexity' (Citroni and Karrholm, 2017). It is easy to argue that large-scale, ticketed events inherently compromise the publicness of parks, but following Citroni and Karrhom's (2017: 12) argument, their publicness can be reaffirmed through such violations.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Struggles over events generate debate in the public sphere about what and who parks are for -'visibilising the nature of the territorial complexity' (Citroni and Karrholm, 2017). It is easy to argue that large-scale, ticketed events inherently compromise the publicness of parks, but following Citroni and Karrhom's (2017: 12) argument, their publicness can be reaffirmed through such violations.…”
Section: Discussionmentioning
confidence: 99%
“…This study also revealed some more progressive justifications: challenging traditional conceptions of parks, widening participation, enhancing their relevance and socialising them. These arguments reflect an alternative conception of event outcomes -as 'eventalisation' -that deviates from the dominant narrative of events as vehicles for appropriation (Citroni and Karrholm, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations